How Technical Innovations May Help to Prevent Drug Shortages in Switzerland - Daniel Gygax; Kaspar Eigenmann; Christian Suter; Marianne Hürzeler; Ahmed Mahmoud; Johannes Mosbacher; Norbert Pöllinger (CHIMIA, 2023)
In this work, we investigated the technical feasibility of 'on-demand' production of selected drugs to cover their demand for a time window of 90 days. We focused on two sub-processes 'automated chemical synthesis' and 'formulation in micropellets'  to enable personalized dosing. The production of drugs 'on-demand' is challenging, important, but also attractive. Switzerland could thus gain access to an additional instrument for increasing resilience for supply-critical drugs. The biggest challenge in the case study presented here is the scalability of automated chemical synthesis and the application range of micropellet formulations.